QUALITY OF PEANUT SEEDS PRODUCED WITH DIFFERENT IRRIGATION LEVELS DURING STORAGE (REMUNOM, 2026)
The use of quality seeds in the field is essential for satisfactory production results. Also, proper seed production management combined with the processing can result in a product of considerable quality. With such practices correctly implemented, savings are achieved during the production process, culminating in a quality seed at a lower cost to the producer. Therefore, this study aimed to evaluate the effects of different irrigation depths over the storage period, in order to verify the appropriate treatment that provides better peanut seed quality. The treatments were defined by seeds treated with five different irrigation depths (l0, l1, l2, l3, l4). The seeds were subsequently evaluated, after harvesting and drying, every four months during twelve months of storage. Quality assessments were based on moisture content, thousand-grain weight, bulk weight, germination, electrical conductivity, and germination speed index. The data obtained in this study showed that the use of irrigation with different water depths did not influence seed vigor and quality. Despite this, water depth l4 was the best treatment in terms of seed germination and vigor. It was observed that storage is a factor of greater importance for preserving seed quality.